Thrombin activation of endometrial endothelial cells: A possible role in intrauterine growth restriction - Krikun, Graciela; Huang, Se-Te Joseph; Schatz, Frederick; Salafia, Carolyn; Stocco, Carlos; Lockwood, Charles J (Thrombosis and Haemostasis, 2007)
Preeclampsia (PE), intrauterine growth restriction (IUGR) and abruption with or without fetal loss are associated with reduced uteroplacental blood flow, decidual vasculopathy, endothelial cell dysfunction, thrombosis, inflammation and hemorrhage. Our hypothesis is that reduced uteroplacental blood flow causes focal decidual hypoxia that generates vascular endothelial growth factor (VEGF). The latter acts directly on decidual endothelial cells to induce aberrant expression of tissue factor (TF), the primary initiator of coagulation. This in turn generates thrombin that induces: i) further TF expression; and ii) inflammatory cytokines. BothVEGF and TF induce aberrant angiogenesis-vessel maintenance reflected by endothelial cell fenestrations and induction of a prothrombotic surface causing both the decidual hemorrhage (i.e.abruption) and thrombosis (i.e.uteroplacental vascular insuf- ficiency) observed in these adverse pregnancy outcomes. This novel hypothesis is supported by our finding of TF expression in decidual endothelium of pregnancies complicated by IUGR and/ or fetal loss. Moreover, treatment of cultured endometrial endothelial cells with VEGF or thrombin induces TF protein and mRNA expression. Quantitative RT-PCR analysis indicates that thrombin enhances (>10-fold) the output of diverse inflammatory cytokines in these cultures. The greatest effect (>2-log) was seen on macrophage inflammatory protein 3 α (MIP3 α ). In vitro, thrombin results in endometrial endothelial cell aggregations and changes in the apoptotic pathway. Thus, we postulate that reductions in uteroplacental flow initiate a cascade of molecular effects leading to hypoxia, thrombosis, inflammation, and endothelial cell dysfunction resulting in untoward pregnancy outcomes.
Keywords: Angiogenesis and inhibitors; pregnancy; inflammation; haemostasis; cytokines